Investigating Indirect and Direct Reputation Formation in Asian Elephants (Elephas maximus) - Jim, Hoi-Lam; Range, Friederike; Marshall-Pescini, Sarah; Dale, Rachel; Plotnik, Joshua M. (Frontiers in Psychology, 2021)
Reputation is a key component in social interactions of group-living animals and appears to play a role in the establishment of cooperation. Animals can form a reputation of an individual by directly interacting with them or by observing them interact with a third-party, i.e., eavesdropping. Elephants are an interesting taxon in which to investigate eavesdropping as they are highly cooperative, large-brained, long-lived terrestrial mammals with a complex social organization. The aim of this study was to investigate whether captive Asian elephants (Elephas maximus) could form reputations of humans through indirect and/or direct experience in two different paradigms: 1) a cooperative string-pulling task and 2) a scenario requiring begging. Fourteen captive Asian elephants in Thailand participated in an experimental procedure that consisted of three parts: baseline, observation and testing. In the observation phase, the subject saw a conspecific interact with two people – one cooperative/generous and one non-cooperative/selfish. The observer could then choose which person to approach in the test phase. The elephants were tested in a second session 2-5 days later. We found no support for the hypothesis that elephants can form reputations of humans through indirect or direct experience, but these results may be due to challenges with experimental design rather than a lack of capacity. We discuss how the results may be due to a potential lack of ecological validity in this study and the difficulty of assessing motivation and attentiveness in elephants. Furthermore, we highlight the importance of designing future experiments that account for the elephants’ use of multi-modal sensory information in their decision-making.